Erratum: Dispersion-engineered nanocomposites enable achromatic diffractive optical elements (Optica (2019) 6 (1031-1038) DOI: 10.1364/OPTICA.6.001031) - Werdehausen, Daniel; Burger, Sven; Staude, Isabelle; Pertsch, Thomas; Decker, Manuel (Optica, 2020)
This publisher's note reports a correction to Optica 6, 1031 (2019).
CRIS-Team Scopus Importer:2023-04-20